Cinema-atlas of the USSR: Far Away in Asia by Vladimir Erofeev / Киноатлас СССР: «Далеко в Азии» Владимира Ерофеева - GOLOVNEV IVAN A. / ГОЛОВНЕВ И.А. (Наука телевидения, 2024)
The proposed research paper serves two purposes. Firstly, it introduces the ethno-geographical documentary titled Far Away in Asia (1931) into scientific discourse. Secondly, it sheds light on the lesser-known theoretical works of the classic of Soviet cinema Vladimir Erofeev, who explored the Soviet/Marxist cinema language. This film is examined in the context of a comprehensive interdepartmental program of the late 1920s to early 1930s, known as the Cinema-Atlas of the USSR. The program aimed to create a 150-episode visual almanac about the diverse nationalities and regions of the Union. Its objective was to construct images in the public consciousness of a multinational, friendly, and progressively developing socialist nation, both for domestic and international film distribution. Methodologically, this article develops the application of the author’s approach to analyze films as cinematic texts: using the chosen example, it demonstrates how the film document can be read as a historical source. The findings highlight the significance of historical cinema documents as multi-layered evidence of visual history, offering informative potential for research across a wide range of humanitarian disciplines. Additionally, the retrospective study of the complex theoretical and practical developments of the early Soviet period is deemed relevant for contemporary screen projects, including scientific, cinematic, and television endeavors. Предлагаемое исследование, с одной стороны, вводит в научный оборот этно-географический кинодокумент «Далеко в Азии» 1931 года, с другой, — малоизвестные теоретические работы классика советского кинематографа В.А. Ерофеева, связанные с поисками в области советского/марксистского киноязыка. Рассмотрение фильма проводится в контексте параллельной масштабной межведомственной программы рубежа 1920–1930-х по реализации большого государственного проекта «Киноатлас СССР», направленного на создание 150-серийного визуального альманаха о народностях и регионах страны и призванного конструировать в общественном сознании образы многонациональной, дружной, прогрессивно развивавшейся при социализме страны — для внутреннего и зарубежного кинопроката. В методологическом плане статья развивает на выбранном примере применение авторского подхода к анализу фильма как кинотекста — в порядке демонстрации опции прочтения кинодокумента как исторического источника. Делаются выводы об исторических кинодокументах как многослойных свидетельствах визуальной истории, обладающих информативным потенциалом для исследования в широком спектре гуманитарных дисциплин, а также о востребованности ретроспективного изучения комплекса теоретико-практических разработок раннесоветского периода для применения при реализации современных экранных проектов, включая научные, кинематографические и телевизионные.